2012
DOI: 10.1016/j.respe.2012.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against seasonal flu in Switzerland: The indecision of pregnant women encouraged by healthcare professionals

Abstract: The recommendation for seasonal flu immunization from the second trimester of pregnancy, adopted in summer 2010 in Switzerland, is situated within a social context characterized by reluctance toward some vaccinations, a relatively low vaccination coverage against flu in the general population, and still heated debates fuelled by vaccination campaigns organized around the A(H1N1)pdm09 flu pandemic in winter 2009 to 2010. This study examines Swiss pregnant women's representations of the risks associated with sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 16 publications
1
42
0
2
Order By: Relevance
“…It is also important to consider comparison with others international similar studies which showed a high level of skepticism about Influenza vaccination, that remains a global public health problem which demands specific strategies and a particular focus on pregnant women as a high‐risk category …”
Section: Discussionmentioning
confidence: 99%
“…It is also important to consider comparison with others international similar studies which showed a high level of skepticism about Influenza vaccination, that remains a global public health problem which demands specific strategies and a particular focus on pregnant women as a high‐risk category …”
Section: Discussionmentioning
confidence: 99%
“…The recommendation is far more effective if combined with the offer of vaccination . Despite this and the proven benefits of antenatal influenza vaccination for both mothers and babies, antenatal care providers are often reluctant to recommend, do not recommend or do not provide access to influenza vaccination in routine antenatal care settings, thus creating structural barriers where pregnant mothers have to make an appointment to attend a separate, usually GP, clinic and pay an additional consultation fee to obtain influenza vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported a perceived lack of information [35,75], misunderstandings [48,74], beliefs that the vaccine is developed too quickly every year [49], and negative information about vaccine safety in the media [69,71]. Perceptions were reported to be influenced by a negative previous experience with the vaccine [34,68], and advice from others against vaccination [62,68]. Finally, some studies discussed the balance (or imbalance) of risk perceptions over perceived benefits of vaccination [61,74], fear of injections [34], adjuvants [73], and/or a preference for homeopathy [37].…”
Section: Seasonal Influenza Vaccinesmentioning
confidence: 99%